Kinetic mechanism of FeCr2O4 reduction in carbon-containing iron melt - Xiao, Yiyu; Wang, Lijun; Liu, Shiyuan; He, Xiaobo; Chou, Kuo-Chih (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Direct alloying of chromium by chromite attracts a lot of interest for its superiority in energy-saving and process simplification. The knowledge of chromium alloying by reduction of FeCr2O4, the main component of chromite, is key to understanding the mechanism of chromium alloying from chromite. The effect of melt composition (carbon and chromium addition) and temperature on the reduction of FeCr2O4 by carbon-containing iron melt was studied. The higher the carbon content is in the melt, the higher chromium recovery is obtained. Similarly, the higher temperature is favourable for the reduction of FeCr2O4. The reduction of FeCr2O4 was impeded by chromium addition due to the lower activity of carbon resulting from the strong attraction between carbon and chromium. The kinetics of FeCr2O4 reduction by carbon dissolving in iron melt were investigated, and the results indicated that the controlling step is the chemical reaction at the FeCr2O4/melt interface at 1550℃. And the calculated activation energy for the chemical reaction is 392.82 kJ/mol.
Keywords: Chromium alloying; Chromite ore; FeCr2O4; Stainless Steel